Peningkatan Pengetahuan Ibu Hamil Tentang Tanda Dan Gejala Keguguran (Miskram) Melalui Kelas Edukasi Antenatal - Adisty Dwi Treasa; Vonny Polopadang; Aisyah Vitariani G; Fanny Astuti; Ni Luh Gede Sri Wahyudianti; A. Eka Ridha Suhartini Yusuf (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Miscarriage is one of the complications of pregnancy that can cause morbidity and even mortality in mothers. Pregnant women's lack of knowledge about the signs and symptoms of miscarriage often leads to delayed treatment. This community service activity aims to increase pregnant women's knowledge about the signs and symptoms of miscarriage through antenatal education classes. The activity was conducted by faculty members and students from the Midwifery Program at Posyandu X in September 2025. The implementation method included a pre-test, interactive education, and a post-test. The results showed an increase in the average knowledge score from 63.2% in the pre-test to 88.6% in the post-test. It can be concluded that antenatal education classes are effective in increasing pregnant women's knowledge about the signs and symptoms of miscarriage.